Accuracy of half-way mucosa-supported implant guides for edentulous jaws: a retrospective study with a median follow-up of 2 years - Tang, Weiwei (J Int Med Res, 2021)
OBJECTIVE: To assess the accuracy of half-way digital mucosa-supported implant guides (HDMIGs) for edentulous jaws. METHODS: Ninety-five consecutive patients (859 implants) with edentulous jaws who underwent implant placement using an HDMIG from July 2012 to June 2018 were retrospectively identified. The primary endpoint was implant-related complications (nerve injury and unexpected perforation), and the secondary endpoints were the faciolingual distance, mesiodistal distance, buccolingual angle, and mesiodistal angle. Follow-ups occurred at 1 month, 2 months, and then every 2 months following implant placement. RESULTS: Twenty-seven (28.4%) patients met the exclusion criteria, leaving 68 eligible patients (636 implants) for the final analysis. The median follow-up was 24 months (range, 18–27 months). No patients developed nerve injury, revision, or unexpected perforation. At the final follow-up, the mean faciolingual distance was 0.65 ± 0.16 mm, the mean mesiodistal distance was 1.16 ± 0.61 mm, the mean buccolingual angle was 4.04° ± 2.26°, and the mean mesiodistal angle was 3.75° ± 2.56°. In the comparison of the first month after surgery and the last follow-up, no significant differences were detected in any of the four measured variables. CONCLUSION: Use of an HDMIG may be a convenient and safe method to ensure correct implantation.